Structural and Semantic Features of People’s Memoirs in Internet Communication - O. V. Minina (Научный диалог)
People’s memoirs as a speech genre of Internet communication are discussed. The definition of people’s memoirs is given as memoirs, the author of which is not a professional writer, but an ordinary native speaker. The purpose of the author is dictated, firstly, by the linguistic interest in the study of memoirs from the perspective of one of the most actively developing directions of modern linguistics - genre studies within the context; secondly, by the need of studying the laws of change of the traditional (which had originally a paper base) genres in the process of developing the new communication space. The novelty of the research is seen in the fact that for the first time in this paper, Internet-genre of people’s memoirs acts as a linguistic object of study - along with existing philological tradition of the study of literary genre and traditional speech genre beyond the professional literary creativity. The structural-semantic parameters of Internet-genre of people’s memoirs are analyzed according to genre model developed by L. Yu. Shipitsina. In the framework of the description of these parameters the structural organization of the genre is set and described, as well as the content embodied in its structural elements. It is proved that the structural and substantial features of Internet genre of people’s memoirs are subject to modification compared to the traditional genre of people’s memoirs with a paper substrate.